Kedudukan dan Peran Ahl Al-Hall wa Al-‘Aqd serta Relevansinya pada Kinerja DPR - Huda, Muhamad Nurul (UIN Sunan Kalijaga Yogyakarta, 2022)
Abstract: In the government system, there are institutions that function as the channel for the voices of the people's aspirations. The Indonesian government system is known as the People's Representative Council while in the Islamic government system it is known as Ahl Al-Hall Wa Al-Aqd. The People's Representative Council is a people's representative institution that accommodates people's aspirations. Meanwhile, ahl al-hall wa al-aqd can be interpreted as those who have the authority to loosen and bind. And also the people in it are influential people. His every decision is binding on those who appointed him. Because they are considered to have more ability in it. The position and role of this institution is very strategic in the government system, ahl al-hall wa al-aqd in carrying out its position and role has a relationship with the performance of the DPR. The problem in this research is First, what is the position and role of the ahl al-hall wa al-aqd and the DPR. Second, what is the relevance of the position and role of ahl al-hall wa al-aqd to the performance of the DPR. This research is a type of library research (library research), this research is descriptive comparative, using a normative approach. The position of the ahl al-hall wa al-aqd institution is at the same level as the government, it is this assembly that conducts deliberations on legal issues and helps the caliph carry out state government. The role of the ahl al-hall wa al-aqd is to nominate, elect and inaugurate the caliph, consult to resolve problems and make regulations. Meanwhile, the position of the DPR as a high state institution means that it is the same as other government institutions, to supervise each other between institutions so that fraud does not occur. The role of the DPR is to form laws, absorb, collect and follow up on people's aspirations. The conclusion of this research is that the two institutions have an equal position in the government system, which is equivalent to other government institutions. And in general they have a relationship in carrying out their position and role in the government system.Keywords: Government, DPR, and Ahl Al-Hall Wa Al-‘AqdAbstrak: Sistem pemerintahan terdapat lembaga yang berfungsi sebagai penyalur suara aspirasi rakyat. Sistem pemerintahan Indonesia dikenal dengan nama Dewan Perwakilan Rakyat sedangkan dalam sistem pemerintahan Islam dikenal dengan sebutan Ahl Al-Hall Wa Al-Aqd. Dewan Perwakilan Rakyat merupakan lembaga perwakilan rakyat yang menampung aspirasi masyarakat. Sedangkan ahl al-hall wa al-aqd dapat diartikan dengan orang-orang yang mempunyai wewenang melonggar dan mengikat. Dan juga orang berada didalamnya adalah orang-orang yang berpengaruh. Setiap keputusannya mengikat orang-orang yang mengangkatnya. Karena mereka di anggap mempunyai kemampuan lebih didalamnya. Kedudukan dan peran lembaga ini sangat strategis dalam sistem pemerintahan, ahl al-hall wa al-aqd dalam menjalankan kedudukan dan perannya memiliki hubungan dengan kinerja DPR. Masalah dalam penelitian ini adalah Pertama, bagaimana kedudukan dan peran ahl al-hall wa al-aqd dan DPR. Kedua, bagaimana kedudukan dan peran ahl al-hall wa al-aqd relevansinya pada kinerja DPR. Penelitian ini termasuk jenis penelitian kepustakaan (library research), penelitian ini bersifat deskriptif komparatif, dengan menggunakan metode pendekatan normatif. Kedudukan lembaga ahl al-hall wa al-aqd ini setingkat dengan pemerintah, majelis inilah yang melakukan musyawarah dalam masalah hukum dan membantu khalifah melaksanakan pemerintah negara. Peran ahl al-hall wa al-aqd mencalonkan, memilih, dan melantik khalifah, bermusyawarah untuk menyelesaikan permasalahan dan membuat peraturan. Sedangkan kedudukan DPR sebagai lembaga tinggi negara artinya sama seperti lembaga pemerintah lainnya, untuk saling mengawasi antar lembaga agar tidak terjadi penyelewengan. Peran DPR membentuk undang-undang, menyerap, menghimpun, dan menindaklanjuti aspirasi masyarakat. Kesimpulan dari penilitian ini, kedua lembaga tersebut memiliki persamaan kedudukan dalam sistem pemerintahan yaitu setara dengan lembaga pemerintah lainnya. Dan secara umum mereka mempunyai hubungan dalam menjalankan kedudukan maupun perannya dalam sistem pemerintahan.Kata kunci : Pemerintah, DPR, dan Ahl Al-Hall Wa Al-Aqd